Challanges in Multilingual Classroom - Romadhona, Zulfa Diana; Ariyanti, Septika; Gustianing, Defy (English Education Department, 2025)
The increasing presence of multilingual learners in diverse educational contexts has brought new challenges for language teaching worldwide. This literature review aims to synthesize key findings from these three perspectives to clarify recurring challenges, identify pedagogical gaps, and justify the need for innovative approaches to support multilingual education. The review employs a qualitative thematic synthesis of the selected articles, organizing the analysis around common themes such as monolingual teaching ethos, translanguaging implementation, teacher identity, and institutional limitations. The findings show consistent evidence that language teachers often struggle to balance political multilingual policies with classroom realities shaped by monolingual pedagogical traditions. While translanguaging is promoted as a potential bridge between students’ diverse linguistic repertoires and school expectations, its effective practice remains hindered by unclear goals, teacher discomfort, and insufficient institutional support. Moreover, the context of Pakistan illustrates how limited classroom time, lack of exposure, and inadequate training further complicate multilingual teaching practices at the secondary level. Overall, this review underscores the urgent need for systemic teacher training, the development of flexible multilingual pedagogies such as translanguaging, and supportive institutional frameworks to align policy goals with practical realities in multilingual education.